PENGARUH MODEL PEMBELAJARAN INKUIRI DAN KEMANDIRIAN TERHADAP PRESTASI BELAJAR SISWA - Wasono Wasono (DIADIK, 2022)
The purpose of this study was to describe the effect of using guided and conventional inquiry models on student achievement in sound material, To describe the effect of independence on student achievement in sound material,To describe the effect of increasing student learning achievement on sound material. In this study, a factorial design was used. The research subjects were fourth grade students at SD Negeri 72 Kota Pagaralam. The data collection techniques used in the study were assessment sheets and student test results. The data analysis used mean and t-test. The conclusions of this research are;There is a difference in learning achievement between students who follow guided inquiry learning models and those who take conventional learning,  There is an effect of guided inquiry learning model and independence on student learning achievement, There is an interaction effect between learning models and independence on student achievement